Website Creation Training for Employees as a Media Information at BSI Solusi Hijau, Bogor Regency - Fajar Rahayu; Andhika Octa Indarso; Windhiadi Yoga Sembada (Institut Teknologi Nasional, Bandung, 2023)
Solusi Hijau wants to develop website as a means to disseminate environmental hygiene programs to inform people that they can save money from the waste they produce. However, at the moment BSI Solusi Hijau does not have any official website, and wants to develop a pilot project utilizing website as an information medium that has wider positive impact and reaches more waste bank customers. This community service activity was held by the UPN Veterans Jakarta Lecturer team at the BSI Solusi Hijau aiming at improving its employee skills, especially in creating an official website. It is hoped that after receiving training on website creation, all employees will be able to independently develop and manage its own website.